KONSEP PERJANJIAN PERKAWINAN DALAM PERSPEKTIF HUKUM ISLAM - Pater, Rizki Anla; Akbarizan, Akbarizan; Munir, Akmal Abdul (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
A marriage contract is a written agreement between prospective husband and wife that aims to regulate rights and obligations in household life, especially the management of assets. This study aims to examine the concept of a marriage contract in Islamic law in Indonesia and Malaysia, two countries with a majority Muslim population. In addition, it compares the regulation of marriage contracts in Islamic law in both countries, analyzes the practice of implementing marriage contracts in both countries, and examines the conformity between regulations and practices with the principles of Islamic law in the context of a marriage contract. This study uses a normative legal research approach that focuses on legal analysis. Here, Islamic law, and more specifically, prenuptial agreements, are the main subject of analysis. The results of this study show that Malaysia has different provisions regarding marriage contracts, Indonesia allows agreements before or during the marriage contract, while Malaysia requires ratification by the Sharia Court. Both countries recognize the importance of taklik talak and property regulations in the agreement. The Indonesian legal system offers flexibility for agreements, but its implementation faces challenges in public understanding and court inconsistencies. Malaysia's legal force is stronger because of mandatory ratification by the Sharia Court, providing higher legitimacy and guarantees.